Handbook of sociology of aging - Settersten, Richard A.; Angel, Jacqueline L.; SpringerLink (Online service). (New York, NY Springer New York Imprint: Springer, 2011)
The Handbook of Sociology of Aging is the most comprehensive and engaging treatment of the field over the past 30 years. It is an indispensable resource for scholars, policy makers, and aging professionals alike. The Handbook of Sociology of Aging contains 45 far-reaching chapters, authored by nearly 80 of the most renowned experts, on the most pressing topics related to aging today. With its recurring attention to the social forces that shape human aging, and their social consequences and policy implications of it, the contents will be of interest to everyone who cares about what aging means for individuals, families, and societies. Two forwards highlight the significance of the handbook for scholarship and and policy-making on aging. The chapters illustrate the field?s extraordinary breadth and depth, which have never before been represented in a single volume. They range from foundational matters, including classic and contemporary theories and methods, to topics of longstanding and emergent interest, such as social diversity and inequalities, social relationships, social institutions, economies and governments, social vulnerabilities, public health, and care arrangements. The volume closes with a set of personal essays by senior scholars who share their experiences and hopes for the field, and an essay by the editors that previews some of the most exciting aspects for the decade ahead. The Handbook of Sociology of Aging showcases the very best that sociology has to offer the study of human aging.
Preface.- Scholarly Foreward.- Policy Foreward.- I. HISTORICAL TRENDS IN THE SOCIOLOGY OF AGING.-Trends in the Sociology of Aging: Thirty Year Observations.- II.THEORIES AND METHODS IN THE SOCIOLOGY OF AGING.- Theoretical Perspectives on the Sociology of Aging.- Aging Individuals, Families, and Societies: Micro-Meso-Macro Linkages in the Life Course.- Widening the View: Capturing Unobserved Heterogeneity in Studies of Age and the Life Course.- III.SOCIAL DIVERSITY AND INEQUALITIES OF AGING.- Gender and Aging.-Race, Ethnicity, and Aging.- Immigration, Aging, and Health in the United States.-Global Aging.- Diversity and Family Relations in an Aging Society.- IV. SOCIAL RELATIONSHIPS AND AGING.- Social Relations and Aging.- Intergenerational Relations in Later-Life Families.- The Midlife Financial Squeeze: Intergenerational Transfers of Financial Resources within Aging Families.- The Demography of Unions Among Older Americans, 1980-Present: A Family Change Approach.- V.SOCIAL INSTITUTIONS AND AGING.- Rethinking Retirement.- Learning and Aging.- The Midlife Years: Human Capital and Job Mobility.- The Changing Worlds of Family and Work.- Developing Age-Friendly Communities: New Approaches to Growing Old in Urban Environments.- VI. ECONOMIES, GOVERNMENT, AND AGING.- Crises and Old Age Politics.-Welfare States: Protecting or Risking Old Age. -Volunteering in Later Life: From Disengagement to Civic Engagement.- Business and Aging: The Boomer Effect on Consumers and Marketing.- Consumption and Aging.-VII. SOCIAL VULNERABILITIES AND AGING.-Planning for Old Age.- Responses of the Long-Term Care System to Recent Natural Disasters.-Elder Mistreatment.- Crime, the Law, and Aging. -Aging Veterans: Needs and Provisions.- VIII. PUBLIC HEALTH AND AGING.- Health and Aging: Early Origins, Persistent Inequalities?.- Mental Health and Aging: A Life-Course Perspective.- Aging with HIV/AIDS.- Obesity: A Sociological Examination.- Religious Involvement, Health Status, and Mortality Risk.- IX. CARE ARRANGEMENTS AND AGING.- Civil Society and Eldercare in Post-Traditional Society.- Population Aging, Health Systems, and Equity: Shared Challenges for the United States and Canada.-Long-Term Care: Tradition and Innovation.- Caregiving and the Life Course: Connecting the Personal and the Public.- X. SOCIOLOGICAL LIVES: PERSONAL REFLECTIONS ON THE SOCIOLOGY OF AGING.- Gerontology with a J: Personal Reflections on Theory-Building in the Sociology of Aging.- The Sociology of Aging and the Life Course Comes of Age.- Long Time Coming, Not Here Yet: The Possibilities of the Social in Age and Life Course Studies.- Looking Back: My Half Century as a Sociologist of Aging and Society.- As Time Goes By: Gerontological and Life Course Musings.- Studying Age Across Borders.- Living the Gendered Life Course in Time and Space.- XI. THE FUTURE OF THE SOCIOLOGY OF AGING- Sociology of Aging in the Decade Ahead.- About the Editors and Contributors.
Electronic reproduction.
Keywords: Aging -- Handbooks, manuals, etc; Sociology -- Handbooks, manuals, etc; Gerontology -- Handbooks, manuals, etc; Older people -- Social conditions -- Handbooks, manuals, etc; Electronic books